2002
DOI: 10.1128/cdli.9.6.1313-1317.2002
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Endoscopy Patients in Ladakh, India, to Helicobacter pylori Whole-Cell and CagA Antigens

Abstract: Although Helicobacter pylori is a cosmopolitan colonizer of the human stomach, the responses among persons in remote populations from whom H. pylori was cultured have not been studied. We report on studies of 189 persons in the Ladakh region of India in whom serum immunoglobulin G responses to H. pylori whole-cell and CagA antigens were measured. H. pylori was isolated from 68 of these patients. An H. pylori whole-cell antigen derived from Ladakhi strains outperformed a similar antigen from U.S. strains, as de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 32 publications
5
52
0
Order By: Relevance
“…Other studies indicated that although antigenic variations do occur, they might not represent a major problem in serology (6,7). In a very recent study from India, however, the same group reported findings similar to ours, i.e., that local strains gave a higher sensitivity in a sonicate whole-cell ELISA (13). Our study thus confirms the observation of that study and expands it by showing that local strains will also result in a higher specificity.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Other studies indicated that although antigenic variations do occur, they might not represent a major problem in serology (6,7). In a very recent study from India, however, the same group reported findings similar to ours, i.e., that local strains gave a higher sensitivity in a sonicate whole-cell ELISA (13). Our study thus confirms the observation of that study and expands it by showing that local strains will also result in a higher specificity.…”
Section: Discussionsupporting
confidence: 79%
“…Whether antigenic differences are important enough to influence diagnostic performance of serological assays has been debated (3,6,7,13). Early studies from Thailand indicated that assays based on local strains performed better than strains of other origin or commercial assays (3).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who were negative for both antibodies (WCÀ, CagAÀ) were classified as H. pylori seronegative, whereas individuals who were seropositive for either WC or CagA antibodies were classified as H. pylori seropositive. This classification system was selected because culture-based studies have shown that individuals who are negative for H. pylori WC antibodies but positive for CagA antibodies are true positives (Romero-Gallo et al, 2002). Seropositive individuals were further classified as carrying CagA-negative strains (WC þ , CagAÀ) or CagA-positive strains (WC þ or WCÀ, CagA þ ) (Romero-Gallo et al, 2002).…”
Section: Serologic Assaysmentioning
confidence: 99%
“…This ELISA has a sensitivity of 94.4% and a specificity of 92.5% (47) and also has been validated in multiple diverse populations (23,43,68). H. pylori culture-positive persons may be seropositive in the CagA assay in the absence of response to the WC antigen (54).…”
Section: Methodsmentioning
confidence: 99%